2019
DOI: 10.1123/jmld.2019-0015
|View full text |Cite
|
Sign up to set email alerts
|

Real World Tracking of Modified Ride-On Car Usage in Young Children With Disabilities

Abstract: Background: Go Baby Go is a community program that provides modified ride-on cars to young children with disabilities. Aims: (1) To describe the real world modified ride-on car usage of young children with disabilities; (2) To compare subjectively reported modified ride-on car usage recorded by parents with objectively reported usage based on electronic tracking data. Methods: 14 young children (1–3 years old) with disabilities used a modified ride-on car for three months. Results: On average, parent-reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…This suggests that cars are primarily used for short-term play with breaks. Previous research indicated that MROCs were used once per day for 17.8 (SD = 9.9) minutes per session on average, 24 which is similar to our results. Despite this similarity, there remained widely variable MROC use among participants in this study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This suggests that cars are primarily used for short-term play with breaks. Previous research indicated that MROCs were used once per day for 17.8 (SD = 9.9) minutes per session on average, 24 which is similar to our results. Despite this similarity, there remained widely variable MROC use among participants in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, initial car use trends appear consistent with caregiver-reported use, suggesting acceptable accuracy of remote tracking as well as revealing relatively infrequent use of MROCs on average in both instances. This is also in agreement with previous research, which found that although families may have under- or overreported MROC use, on average, there was no significant difference between reported and recorded use 24. Additionally, although bout duration and play session length varied widely between participants, the majority of bouts lasted for 1- to 10-minute increments.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The 30-minute driving session will involve the participants learning cause-effect concepts by driving the modified ride-on car (i.e., pressing the switch for moving and releasing it for stopping). The dose of the intervention will be adjusted considering the opinion of the parents who participated in a previous interview and the results of a recent study, where the average time of interventions was 24 to 30 min [37]. The therapist and caregivers then will use verbal and physical cueing to encourage children to drive and explore the surrounding environment [17,38].…”
Section: Interventionmentioning
confidence: 99%